2022
DOI: 10.1038/s41467-022-31478-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-voltage operation of light-emitting diodes

Abstract: For a light-emitting diode (LED) to generate light, the minimum voltage required is widely considered to be the emitter’s bandgap divided by the elementary charge. Here we show for many classes of LEDs, including those based on perovskite, organic, quantum-dot and III–V semiconductors, light emission can be observed at record-low voltages of 36–60% of their bandgaps, exhibiting a large apparent energy gain of 0.6–1.4 eV per photon. For 17 types of LEDs with different modes of charge injection and recombination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 58 publications
1
44
0
Order By: Relevance
“…Appreciable light emission can be observed even if the potential energy of carriers decreases further to 2.2 eV, which means that carriers can somehow overcome the potential barrier for injection into the active region, which is not offset completely by the applied voltage. [ 15–17 ] This phenomenon is not unique to Micro‐LEDs and can also be found in SSL LEDs and even FETs. [ 18 ] More specifically, a drain current can be registered even though the applied gate voltage is smaller than threshold voltage, which is called “subthreshold leakage.” However, things get more complicated for light‐emitting devices because a considerable carrier density should be established in the active region so that the generation rate of photons can exceed self‐absorption losses.…”
Section: Scientific Challenges and Possible Solutionsmentioning
confidence: 99%
“…Appreciable light emission can be observed even if the potential energy of carriers decreases further to 2.2 eV, which means that carriers can somehow overcome the potential barrier for injection into the active region, which is not offset completely by the applied voltage. [ 15–17 ] This phenomenon is not unique to Micro‐LEDs and can also be found in SSL LEDs and even FETs. [ 18 ] More specifically, a drain current can be registered even though the applied gate voltage is smaller than threshold voltage, which is called “subthreshold leakage.” However, things get more complicated for light‐emitting devices because a considerable carrier density should be established in the active region so that the generation rate of photons can exceed self‐absorption losses.…”
Section: Scientific Challenges and Possible Solutionsmentioning
confidence: 99%
“…Di and co-workers used high-sensitivity photodetectors to study the threshold voltages in LEDs and measured the apparent threshold voltages at which the minimum photon flux can be detected. 12 Due to the ultrahigh sensitivity, the apparent threshold voltages can be further decreased from ∼0.8E g /e to 0.5E g /e or even lower (here E g is the bandgap of the EML and e is the elementary charge), providing solid evidence of the universality of sub-bandgapvoltage EL in LEDs. What's more, derived from the Fermi− Dirac distribution, Di et al 12 constructed a relationship between EL intensity and applied voltage to explain the origin of sub-bandgap-voltage turn-on, and suggested that EL could occur even at voltages approaching zero.…”
mentioning
confidence: 99%
“…The Auger model is frequently applied to explain the sub-bandgap-voltage ELs in quantum dot-, , polymer-, or perovskite-based LEDs. , However, we should mention that this model should not be a dominant mechanism. Generally speaking, high carrier density is needed when the Auger process dominates.…”
mentioning
confidence: 99%
See 2 more Smart Citations